Emergence and functionality of organizational routines: An individualistic approach - Ulrich Witt (Max Planck Institute of Economics, 2009)
The functionality of organizational routines, i.e. the factual value for accomplishing their purposes, is an important constraint on the capabilities an organization can bring to bear on its operations. Often falling short of its potential, the actual make-up of organizational routines invites managerial attention. Of the criteria by which the functionality can be assessed, the generic one discussed in this paper is whose interests this make-up serves. This is determined by the conditions under which organizational routines emerge, particularly the cognitive and motivational attitudes of the organization members involved at this stage. By uncovering how these enhance or impair a routine's functionality for the organization's goals, the paper corroborates the relevance of an individualistic approach in organizational theory.
Keywords: 330; organization; routines; capabilities; knowledge; mental models; motivation